COMBATING DOMESTIC VIOLENCE: THE LEGAL FRAMEWORK FOR PREVENTIVE MEASURES - Dadaboeva Dilfuza Nurmatovna (Modern American Journals, 2025)
Domestic violence remains one of the most urgent social and legal challenges affecting the stability and security of families and society. Despite increasing state attention and legislative reforms, the scale of domestic violence shows that preventive actions must be strengthened and systematized. This article explores the legal framework that regulates prevention mechanisms against domestic violence, emphasizing its role in protecting vulnerable populations, ensuring human rights, and promoting social well-being. The study analyzes existing national legislation, international obligations, and institutional measures aimed at identifying risks, preventing recurrence, and ensuring comprehensive support for victims. Special attention is given to the effectiveness of protection orders, social services, and community-based interventions that aim to eliminate violent behavior before it escalates. The findings reveal both significant legal achievements and persisting gaps, including insufficient enforcement mechanisms, limited victim support infrastructure, and challenges in interagency coordination. The article concludes that preventive legal measures are critical for establishing a safe family environment, strengthening social responsibility, and ensuring long-term reduction of domestic violence cases. The research outcomes may support improvements in state policy, pedagogical awareness, and professional training for future specialists engaged in social protection and educational fields.
Keywords: Domestic violence, legal framework, prevention, victim protection, social services, human rights, protection order, family security, institutional mechanisms.